Acupuncture Alleviated the Nonmotor Symptoms of Parkinson's Disease including Pain, Depression, and Autonomic Symptoms. (31st December 2014) - Iseki, Chifumi; Furuta, Taiga; Suzuki, Masao; Koyama, Shingo; Suzuki, Keiji; Suzuki, Tomoko; Kaneko, Akiyo; Mitsuma, Tadamichi
Abstract : A woman started to feel intractable pain on her lower legs when she was 76. At the age of 78, she was diagnosed as having Parkinson's disease (PD). The leg pain was suspected to be a symptom of PD after eliminating other causes. The patient also suffered from nonmotor symptoms, depression, anxiety, hot flashes, and paroxysmal sweating. Though the patient had received pharmacotherapy including levodopa for 5 years, she still suffered from the nonmotor symptoms and was referred to our department. We treated her with acupuncture based on the Chinese traditional medicine and electroacupuncture five times per week. After the 2-week treatment, the assessment for the symptoms was as follows; visual analogue scale (VAS) score of the leg pain was 16 mm (70 mm, before), Hamilton's rating scales for depression (HAM-D) score was 9 (18, before), timed 3 m Up and Go took 20 steps in 30 sec (24 steps in 38 sec, before), and the Movement Disorder Society-sponsored revision of the Unified Parkinson's Disease Rating Scale (MDS-UPDRS) Part 1 score was 13 (21, before). Autonomic symptoms, hot flashes and paroxysmal sweating, were also alleviated. Acupuncture may be a good treatment modality for nonmotor symptoms in PD.